Evaluation of small cardamom accessions for moisture stress - K S Krishnamurthy, S J Ankegowda, (Journal of Spices and Aromatic Crops, 2008)
High biomass and high yielding cardamom genotypes viz., Green gold, Mysore-2, APG 277,Malabar-18, Compound panicle 7 (CP 7) and Hybrid 36 were screened for moisture stresstolerance. Clonally propagated seedlings were planted in cement pots and grown for one anda half year with recommended package of practices under rainout shelter with three replicationsand two treatments (control and moisture stress). Moisture stress was imposed by withholdingirrigation for two months. Data on morphological and physiological parameters related todrought tolerance were recorded at the initiation, middle and end of stress. Plant height andnumber of leaves per clump did not record significant variation among the accessions at theinitiation of stress. Number of dried leaves increased under stress in all genotypes at themiddle of stress. Compound panicle 7 recorded higher reduction in biomass at end of stressperiod compared to all other accessions. Variation in relative water content between thetreatments was non significant. Chlorophyll florescence yield reduced significantly undermoisture stress treatment compared to control. Results indicate that genotypes Mysore 2,Green gold and Malabar 18 have better adaptability to drought conditions.